2018
DOI: 10.1371/journal.pone.0197778
|View full text |Cite
|
Sign up to set email alerts
|

Meditation or exercise for preventing acute respiratory infection (MEPARI-2): A randomized controlled trial

Abstract: BackgroundPractice of meditation or exercise may enhance health to protect against acute infectious illness.ObjectiveTo assess preventive effects of meditation and exercise on acute respiratory infection (ARI) illness.DesignRandomized controlled prevention trial with three parallel groups.SettingMadison, Wisconsin, USA.ParticipantsCommunity-recruited adults who did not regularly exercise or meditate.Methods1) 8-week behavioral training in mindfulness-based stress reduction (MBSR); 2) matched 8-week training in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 79 publications
4
73
0
1
Order By: Relevance
“…With regard to sIgA, as mentioned previously, no significant differences have been observed between the practice of MM and PE regarding the immunocompetence of IgA, in any of the conducted analyses. Thus, our results are in line with those of other authors who also compared the effects of IgA in MM and PE after inoculation with the flu vaccine [16,72,87,90]. They are also consistent with trials that only analysed IgA in MM, such as the systematic review undertaken by Black and Slaich [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With regard to sIgA, as mentioned previously, no significant differences have been observed between the practice of MM and PE regarding the immunocompetence of IgA, in any of the conducted analyses. Thus, our results are in line with those of other authors who also compared the effects of IgA in MM and PE after inoculation with the flu vaccine [16,72,87,90]. They are also consistent with trials that only analysed IgA in MM, such as the systematic review undertaken by Black and Slaich [15].…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have established longer intervals between measures, of weeks or even months depending on the pre-test and post-test of the intervention. In these cases, sIgA concentrations appear unaffected by the practice [15,16,[72][73][74].…”
Section: Introductionmentioning
confidence: 97%
“…A randomized controlled trial evaluating the preventive effect of aerobic exercises on acute respiratory illness found that participants in exercise group reported lesser episodes of illness compared to participants with sedentary lifestyles. The severity index and total days of illness (duration) showed a lower trend for the exercise group as compared to control [6]. The trial also revealed a decrease in interleukin-8 factor and increase in mean levels of neutrophils in the exercise group.…”
mentioning
confidence: 80%
“…The trial also revealed a decrease in interleukin-8 factor and increase in mean levels of neutrophils in the exercise group. It was also reported that the immunoprotective effect of aerobic exercise can also improve antibody responses to influenza vaccination in sedentary elderly [6] (refer Table 1).…”
mentioning
confidence: 91%
“…With regard to the scope of the study of mindfulness and its effects on neuroinflammation, the biomarkers that have been examined are the pro-inflammatory cytokines interleukin 6 (IL-6) [23][24][25][26], IL-8 [23,27], TNF-α [24][25][26] and interferon gamma (IFN-γ) [28][29][30]; the anti-inflammatory cytokines IL-4 [28] and IL-10 [24]; neuropeptides, such as neuropeptide Y [31]; and CRP [27,32]. In addition, although low-grade inflammation is generally determined by increased levels of high-sensitive CRP (hsCRP) [33,34], it is also reflected by increased concentrations of pro-inflammatory cytokines and acute phase proteins, such as CRP [35].…”
Section: Introductionmentioning
confidence: 99%